2018
DOI: 10.1007/s11060-018-2774-z
|View full text |Cite
|
Sign up to set email alerts
|

The predictive potential of hyponatremia for glioblastoma patient survival

Abstract: Glioblastoma is a devastating malignancy with a dismal survival rate. Currently, there are limited prognostic markers of glioblastoma including IDH1, ATRX, MGMT, PTEN, EGFRvIII, and others. Although these biomarkers for tumor prognosis are available, a surgical biopsy must be performed for these analyses, which has morbidity involved. A non-invasive and readily available biomarker is sought after which provides clinicians prognostic information. Sodium is an electrolyte that is easily and quickly obtained thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…One recent study analyzed the predictive value of hyponatremia in 200 GBM patients. Similar to the results of this study, the authors could not demonstrate an association between hyponatremia and patients' outcome (22). In this cohort of GBM patients, arterial hypertension, diabetes, a higher age, and a poor preoperative clinical status characterized the cohort of patients with hypochloremia.…”
Section: Discussionsupporting
confidence: 85%
“…One recent study analyzed the predictive value of hyponatremia in 200 GBM patients. Similar to the results of this study, the authors could not demonstrate an association between hyponatremia and patients' outcome (22). In this cohort of GBM patients, arterial hypertension, diabetes, a higher age, and a poor preoperative clinical status characterized the cohort of patients with hypochloremia.…”
Section: Discussionsupporting
confidence: 85%
“…Hyponatraemia is a common electrolyte disturbance in critical illness and malignancies. Many prospective and retrospective studies have indicated the occurrence of hyponatraemia and its importance as a prognostic factor in ICU patients [16], acute-on-chronic liver failure [17], glioblastoma [18], and lung cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…Hyponatraemia is a common electrolyte disturbance in critical illness and malignancies. Many prospective and retrospective studies have indicated the occurrence of hyponatraemia and its importance as a prognostic factor in ICU patients [16], acute-on-chronic liver failure [17], glioblastoma [18], and lung cancer [19].…”
Section: Discussionmentioning
confidence: 99%